Defective democracy - Croissant, Aurel; Merkel, Wolfgang (The handbook of political, social, and economic transformation, 2019)
Both new and established democracies have witnessed setbacks in their democratic quality since the turn of the century, while the number of so-called hybrid regimes has increased. The concept of embedded democracy is a conceptual tool to differentiate between liberal democracy and open autocracy. Composed of five analytically separate yet empirically intertwined ‘partial regimes’, the concept of embedded democracy discerns a political regime’s institutional arrangements and its external environment. In addition, the concept allows one to conceptualize and analyse different types of defective democracy within the grey zone between liberal democracy and autocracy. The chapter conceptualizes embedded and defective democracies and engages in a comprehensive analysis regarding the frequency, persistence, origin, and causes of different types of defective democracy in the early twenty-first century.
Gesehen am 18.02.2021